A influência das alterações nasais na adesão ao aparelho de pressão aérea positiva em pacientes com síndrome da apneia obstrutiva do sono - Haddad, Fernanda Louise Martinho [UNIFESP] (2011)
Introduction: Researches showed a higher incidence of nasal disorders in patients with Obstructive Sleep Apnea Syndrome (OSAS) compared to controls, but the correlation between the nasal permeability and positive airway pressure device (CPAP) compliance is controversy in the literature. Furthermore there is no consensus on what would or would be the best methods of assessment of nasal function. Thus, the aim of this study was to evaluate the contribution of nasal alterations in CPAP compliance in patients with OSAS. Method: We included patients of both genders, between 25 to 65 years, with moderate to severe OSAS. The protocol consisted of questionnaires, rhinoscopy, nasofibroscopy, nasal inspiratory peak flow, acoustic rhinometry and polysomnography. The patients received CPAP for home use for 6 months and were followed in an educational program. At the end of 6 months, patients who used CPAP 4 hours or more per night, at least 70% of nights were considered as having good compliance, and the others as having poor compliance.Results: Of 45 patients enrolled, 34 finished the study. Eleven (33.4%) patients were female and 23 (67.6%) males, mean age 53.1 ± 9.1 years. Sixteen (47.1%) patients had good compliance (use 􀂕 4 hours per night). Clinical parameters were significant: body mass index (BMI), neck circumference (NC) and apnea-hypopnea index (AHI) higher (p = 0.030, p = 0.006, p = 0.032), and oxyhemoglobin saturation minimum minor (p = 0.041) in the group with good compliance. Nasal parameters showed no differences between groups. The correlations with the largest number of hours of CPAP use were: higher BMI (p = 0.043), higher NC (P = 0.007), higher AHI (p = 0.043), higher CPAP pressure (p = 0.012), lower average of minimal sectional areas in the supine position (p = 0.029). In the linear regression model, the findings related to the greater number of hours of CPAP use were: higher CC (p = 0.015), higher AHI (p = 0.034), lower notes of nasal symptoms (p = 0.007) and lower volume of nasal cavity in the supine position (p = 0.001). Conclusions: Most nasal parameters evaluated were contradictory or did not influence adherence to CPAP. The parameters that were significantly correlated with adherence to CPAP in this group of OSA patients were clinical and polysomnographic predictors of the presence and severity of OSA.